V̄aṛtika v̄artava / ̄Aṇtạrikkai / Araca Apivirutti Amaippuk K̄ụṭtutt̄apa̲nam = Annual report / State Development & Construction Corporation
Annual report of r̄ajya Sạmvardhana h̄a Nirm̄ana N̄itigata Sạmsth̄ava (Stete development & Construction Corporation)